PENGARUH TAYANGAN MY TRIP MY ADVENTURE TERHADAP MINAT BERWISATA REMAJA KARANG TARUNA KELURAHAN AIRPUTIH KECAMATAN TAMPAN - Didik Syahputra; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The development of the mass media both print and electronic media will bring many changes in society. The most dominant media is television. Private television stations compete to present the best show for the audience. One of them is a documentary program travel and lifestyle My Trip My Adventure served TransTV.The method used in this research is quantitative descriptive. Data collection techniques in this study using a questionnaire. The sample for this study as many as 96 respondents and using purposive sampling techniques with the unknow population formula. Data analysis techniques used is a simple linear regression analysis by using SPSS 23. The theory used in this study is S-O-R Theory, (Stimulus, Organism, Response), show that communication is a process of action-reaction which causes directional effect, immediately and directly to the communicant.The result of research show that the thitung > ttabel (4,723 > 1,985) with significance 0,05, means that Ha is accepted and Ho is rejected, meaning that there is the influence of My Trip My Adventure impressions on Teenage’s interest traveling in Youth Organization Airputih Village on Tampan Subdistrict, with a coefficient of determination 19,2%, meaning that variable My Trip My Adventure impressions can only affect variable teenage’s interest traveling 19,2% and the rest is influenced by other variable which was not included in this study.